Charakter prawny dyplomu ukończenia studiów wyższych w świetle nowelizacji art. 167 ustawy — Prawo o szkolnictwie wyższym - Mrożek, Jakub (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article touches upon the problem of the legal character of higher education diploma. The previous legal standards relating thereto has been considerably changed as a result of the amendment to the Act on higher education, effective as of 1st of October 2011. After abandoning the previous regulations, the present legal status of higher education diploma becomes problematic, especially taking into account European Union rules pertaining to recognition of professional qualifications obtained in the other EU Member States.The thesis of the article is proposed based on a legal analysis of the current wording of the rules of Act on higher education. Then they are juxtaposed with analogous regulations found in other acts and in the provisions of European Union law, as well as with current legal output. The article is concluded by the findings concerning the legal status of higher education diploma, which express the author’s views on the influence of new rules on other regulations and on the present legal knowledge.
Keywords: higher education diploma; national document; Tertiary Education Minister; ordinance; university